2020
DOI: 10.1039/d0bm01398f
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles coated by green graphene quantum dots for accelerating the healing of MRSA-infected wounds

Abstract: Bacterial infection, especially multidrug-resistant bacteria-induced infection, is threatening human health seriously, which has posed great challenges for clinical therapy. The overuse of conventional antibiotics has given rise to bacterial resistance...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Pal et al 45 incorporated Ag NPs into BC by UV light irradiation and got excellent antibacterial results towards E. coli . Zhong et al 46 prepared GQDs@Ag NPs for wound healing treatment. The in vitro and in vivo results demonstrated that GQDs@Ag hybrids with superior biosafety showed a markedly enhanced effect in killing MRSA and accelerating MRSA ‐infected wound healing as compared to AgNPs alone.…”
Section: Discussionmentioning
confidence: 99%
“…Pal et al 45 incorporated Ag NPs into BC by UV light irradiation and got excellent antibacterial results towards E. coli . Zhong et al 46 prepared GQDs@Ag NPs for wound healing treatment. The in vitro and in vivo results demonstrated that GQDs@Ag hybrids with superior biosafety showed a markedly enhanced effect in killing MRSA and accelerating MRSA ‐infected wound healing as compared to AgNPs alone.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2c,d indicated that the temperature increase of OHH NPs could be precisely tuned by the concentration of OHH NPs and/or laser intensity. using the previously reported equation (Zhong et al, 2020) to measure the photothermal conversion efficiency, we found that OHH NPs possessed a relatively high photothermal conversion efficiency of 27.13% (Figure 2e). According to the constant temperature change after through five heating‐cooling cycles, it could be concluded that OHH NPs possessed the high photo‐stability (Figure 2f).…”
Section: Resultsmentioning
confidence: 58%
“…Currently, including noble metal nanomaterials, metal sulfide/oxide nanomaterials, carbon-based nanomaterials, polymer-based nanomaterials, and small molecule-based nanomaterials, they have been widely studied to induce bacterial death through their own physical properties, toxicity, and combined with photothermal therapy (PTT) Gao et al, 2021;Li et al, 2020). At the same time, we also have some outstanding contributions in antibacterial (Tong et al, 2019(Tong et al, , 2020Zhong et al, 2020) aspects of nanoparticle-based combination therapy. Among various antibacterial nanomaterials, Prussian blue (PB) nanoparticles have gained great popularity for PTT due to the eminent advantages of strong NIR radiation absorption ability, high photothermal efficiency, excellent chemical stability, splendid biocompatibility, and low cost (Liu et al, 2021;Tong et al, 2020).…”
mentioning
confidence: 99%
“…To facilitate the description or understanding of which components of an AdMa drive hazard, we use Ag NMs which is coated with graphene-sheets contains Quantum Dots (QDs) as an existing example of a multi-elemental AdMa used as an antibacterial material 29 (Figure 2a). These AdMa consist of stable NMs (the graphene) as well as quickly soluble (Ag NMs) and slowly soluble (QD) fractions.…”
Section: Dynamic Behaviour Of Admamentioning
confidence: 99%